« Vous n'en mangerez point » L'alimentation comme distinction religieuse - Almeida Mendes, Paula (PHR series, 2019)
Using a multidisciplinary, diachronic and comparative methodology, this collective work aims to show how dietary distinctions help us to better understand how a religious system functions.